Pendampingan Manajemen Operasional dalam Meningkatkan Efisiensi Keuangan pada UMKM Warung Pecel Bu Nor di Kabupaten Sidoarjo - Ahmad Alfan Al Azizi (Lembaga Pengembangan Kinerja Dosen, 2026)
Low financial literacy and managerial capability remain common issues faced by micro, small, and medium enterprises (MSMEs), particularly in the culinary sector, which consequently affects financial efficiency and business sustainability. Many business owners still maintain simple and unstructured financial records and often mix personal and business finances, leading to difficulties in determining profit and making appropriate business decisions. This community service activity aims to improve financial efficiency through operational management assistance for the MSME Warung Pecel Bu Nor located in Gading Fajar, Candi District, Sidoarjo Regency. The method used is Participatory Action Research (PAR), which actively involves business owners in every stage of the activity, including problem identification, action planning, implementation, evaluation, and reflection. Data collection techniques include observation, interviews, discussions, and joint reflection. The results indicate an improvement in the business owner’s understanding and skills in simple financial recording, separation of personal and business finances, and operational cost control. In addition, there is an improvement in the organization of business management and managerial awareness. This assistance contributes to increased financial efficiency, business stability, and the potential improvement of the economic welfare of business owners. Overall, this assistance has proven effective in supporting the sustainability of MSMEs; therefore, continuous assistance is needed so that business owners can consistently implement more professional business management practices.